Analisa Efektifitas Penggunaan Base Plate Orfit Pada Kasus Kanker Payudara Posisi Prone Dengan Teknik Intensity Modulated Radiotherapy (IMRT) Di Instalasi Radioterapi Rumah Sakit Daerah Jakarta Timur - Andry Putra Wijaya; I Putu Eka Juliantara; Devina Fikli (Jurnal Ilmu Kesehatan dan Gizi, 2024)
Radiotherapy is a treatment for cancer using high-energy radiation, usually X-rays. The type and amount of radiation received is calculated by oncologists and medical physicists to destroy cancer cells, these cells are abnormal cells. This stops the cancer cells from dividing properly and as a result the cancer cells are destroyed. This treatment is planned to protect healthy tissue as much as possible from radiation which has destructive properties, however some healthy tissue can be affected which will later cause side effects. Radiotherapy uses a Linear Accelerato (LINAC) device in its treatment. The LINAC can produce two beams, namely photons and electrons. Photon beams are usually used to illuminate tumors in deeper tissue in the body, for example breast cancer, cervical cancer and nasopharyngeal cancer, while electron beams are used for cancer therapy in surface tumors. The role of radiotherapy in the treatment of breast cancer has a long and controversial history. One of the first clinical trials ever conducted, it began in 1949, and remains the subject of new trials still being initiated today. Early trials clearly showed that radiotherapy reduced local recurrence, with a relative risk reduction now known to be approximately 70%, but a reduction in recurrence rates did not translate into a reduction in mortality. Theories explaining this difference are numerous, including the detrimental effects of radiotherapy on immune function.